Kesehatan Mental dan Spiritualitas: Bagaimana Konsep Al-Qur’an Menghadapi Krisis Psikologis Era Kontemporer? - Nurusshobah; Akhmad Aidil Fitra (Jurnal test, 2025)
This research examines the link between mental health and spirituality, with a focus on the teachings of the Qur’an, as a response to today’s psychological challenges. The main objective of this study is to analyse how spiritual teachings in the Qur’ān can help individuals overcome psychological problems, such as stress, anxiety and depression, that are increasingly faced by modern society. A qualitative approach (library research) was used in this study to examine Qur’anic verses relating to mental and spiritual health and compare them with contemporary psychological theories. The results show that Qur’anic principles, such as tawakkal (surrender), dhikr (remembrance of God), sabr (patience), and gratitude (thankfulness), are effective in supporting the management of individuals’ psychological and emotional states. The study also emphasised the importance of combining spiritual teachings with modern psychological techniques to create a more holistic approach to mental well-being. Based on these findings, the study concludes that Qur’anic spirituality can be a relevant and effective method in helping individuals overcome psychological crises in the contemporary era.